The long-term integration of refugee children: Swedish experiences after the Yugoslav Wars - Olof Åslund; Linus Liljeberg; Sara Roman (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
We study the economic and social integration of refugee children. The analysis follows war refugees arriving from former Yugoslavia to Sweden in the early 1990s for up to 25 years. We find strong educational and economic integration, although differing by age at migration and gender. By contrast, segregation is striking in family formation. Those under 7 at migration had grades and high school completion on par with natives. Poor initial school performance among teenage refugees was partly compensated by education at higher ages. By 2019 there was on average full labor market assimilation among women while a small gap remained among men. However, refugees arriving before school start outperformed their native peers. Endogamy was common; even among preschoolers, 60-70 percent had their first child with a partner of Yugoslavian descent. Many of the partners migrated after the refugee had turned 20. Intermarriage is gendered and related to socioeconomic status. Residential and workplace segregation decreased over time but remained pronounced among people without tertiary education.
Keywords: F22; J15; J18; 330; Refugee children; migrants; economic and social integration